Estimation of genetic distances and heterosis in three ostrich (Struthio camelus) breeds for the improvement of productivity - Davids, Annelin Henriehetta (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.